AUDIT MUTU DESAIN Studi Kasus Pekerjaan Perencanaan pada Kegiatan Participatory Irrigation Sector Project Kabupaten Banyumas - Chrisna Pudyawardhana (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2007)
AbstractÂ Intend the execution make an audit of the Quality Detain is to specify whether activity of quality of and interconnected result as according to arrangement planned and whether arrangement which have been compiled to be applied effectively and according to for the attainment of target.This study evaluate the document execution plan the quality which have been compiled in course of planning of activity of Participatory Irrigation Sector Project in regency Banyumas.Make an audit of the such Quality Detain cover the phase of preparation of making detain, making design, making of complement work, and use of document design.Â Keyword : Audit of Quality of detain, Consultant, Banyumas.